(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The current study aims to assess the suitability of surface water running in the AlKhasa River, located within the city of Kirkuk, for irrigation purposes. This study applied the Irrigation Water Quality Index (IWQI) and Heavy Metal Pollution Index (HPI) to analyze seasonal changes in contamination levels. To achieve this goal, sixteen samples were collected from the AlKhasa River over one year (2023), distributed across four seasons (four samples per season) to track fluctuations in water quality and determine its characteristics throughout the year. The study relied on two main indices: the Irrigation Water Quality Index (IWQI) and the Heavy Metal Pollution Index (HPI). The drinking water quality index is excluded due to the nature of the water in the river, which consists of a mixture of sewage and rainwater, making it unsuitable for assessment according to drinking water standards. The (IWQI) results reveal that all analyzed samples are of high quality and classified as "very suitable" for irrigation use, with all recording values above (37) confirming their suitability for this purpose. As for (HPI), the results show significant seasonal variation in contamination levels. In winter, the index values range between (61.777 and 90.276), placing most sampling stations in the "poor to very poor" category in terms of contamination, except Station (1), which recorded a "good" level. In contrast, all stations in the other seasons (summer, autumn, and spring) recorded "excellent" levels in terms of water quality, with index values ranging between 6.591 and 18.368, except Station (1) in spring and fall, which recorded a "good" rating. These results demonstrate that heavy metal contamination varies significantly between seasons, with levels significantly higher during winter compared to other seasons.